Overview of clinical outcome and therapeutic effectiveness of Favipiravir in patients with COVID-19 admitted to intensive care unit, Riyadh, Saudi Arabia - Abbas Al Mutair; Jinan Shamou; Saad Alhumaid; Laila Layqah; Gasmelseed Y. Ahmed; Koritala Thoyaja; Mohammed Al Mohaini; Sana Almahmoud; Mazin Barry; Amjad Khan; Kuldeep Dhama; Lamiaa Hamad Al-Jamea; et al. (Elsevier, 2022)
Background: Prior to the availability of the current COVID-19 vaccine, the need to control the pandemic worldwide was focused on management of the disease using previously approved antivirals, including Favipiravir which inhibits viral replication through the RNA dependent RNA polymerase enzyme. Favipiravir's efficacy against different viral infections has made it a potential treatment for COVID-19. We are aiming in this study to assess the therapeutic efficacy and safety of Favipiravir in treating critically ill patients admitted with COVID-19 to Intensive Care Units (ICUs). Methods: This is a retrospective cohort study was conducted in five tertiary hospitals in Riyadh, Kingdom of Saudi Arabia (KSA). The studied sample was randomized from a huge pool of data collected primarily for critically ill COVID-19 patients admitted to (ICUs) during the period between April 2020 to March 2021. Two groups of patients matched 1: 1 for age and body mass index (BMI) was enrolled in the study; one group received Favipiravir and another comparison group received other antimicrobial medications, not including Favipiravir. Results: A total data of 538 COVID-19 patients were analyzed, 269 (50.%) received Favipiravir and 269 (50%) the control group received different treatments. More than two-thirds 201 (74.7%) were Saudi citizens, the majority 177 (65.8%) were males and the mean age and (BMI) were; (57.23 ± 15.16) years and (31.61 ± 7.33) kg/m2 respectively. The most frequent symptoms of presentation were shortness of breath (SOB), fever, and cough, and the most frequent comorbidity was diabetes mellitus, hypertension, and ischemic heart disease.In the supplemental therapy, corticosteroid, tocilizumab and chloroquine were statistically significant (P = 0.001) when combined in the FVP group more than in the comparison group. Severe acute respiratory distress syndrome (ARDS) was more frequent among Favipiravir group, while the overall mortality rate among the Favipiravir group was not statistically significant (p-value 0.4). Conclusion: According to the study's results revealing FVP is not superior to other antivirals, patients who received Favipiravir presented with more severe symptoms, more comorbidities, more complications, and is not effective in controlling the cytokine storm which negatively impact the efficacy of Favipiravir.FVP therapy had no influence on ICU and hospital length of stay in comparison with the control group as well as in the overall mortality rate among the FVP group was not statistically significant. further research is needed to understand how FVP along with other treatments can improve the length of stay among COVID-19 patients admitted to the ICU.